Radical Intermediates in Monooxygenase Reactions of Rieske Dioxygenases - Chakrabarty, Sarmistha (2007)
[Image: see text] Rieske dioxygenases catalyze the cis-dihydroxylation of a wide range of aromatic compounds to initiate their biodegradation. The archetypal Rieske dioxygenase naphthalene 1,2-dioxygenase (NDOS) catalyzes dioxygenation of naphthalene to form (+)-cis-(1R,2S)-dihydroxy-1,2-dihydronaphthalene. NDOS is composed of three proteins: a reductase, a ferredoxin, and an α(3)β(3) oxygenase (NDO). In each α subunit, NDO contains a Rieske Fe(2)S(2) cluster and a mononuclear iron site where substrate dihydroxylation occurs. NDOS also catalyzes monooxygenase reactions for many substrates. The mechanism of the reaction is unknown for either the mono- or di-oxygenase reactions, but has been postulated to involve either direct reaction of a structurally characterized Fe(III)-hydroperoxy intermediate or the electronically equivalent Fe(V)-oxo-hydroxo intermediate formed by O-O bond cleavage before reaction with substrate. The reaction for the former intermediate is expected to proceed through cationic intermediates while the latter is anticipated to initially form a radical intermediate. Here the monooxygenation reactions of the diagnostic probe molecules norcarane and bicyclohexane are investigated. In each case, a significant amount of the rearrangement product derived from a radical intermediate (lifetime of 11–18 ns) is observed while little or no ring expansion product from a cationic intermediate is formed. Thus, monooxygenation of these molecules appears to proceed via the Fe(V)-oxo-hydroxo intermediate. The formation of this high-valent intermediate shows that it must also be considered as a possible participant in the dioxygenation reaction, in contrast to computational studies but in accord with previous biomimetic studies.